Phonological Speech Impairments Due to Anxiety Disorders - Maryam Khawar (Journal of Health, Wellness and Community Research, 2025)
Background: Anxiety disorders are among the most prevalent mental health conditions worldwide, and their effects extend beyond emotional and cognitive domains to communication. Phonological speech impairments, including stuttering, cluttering, reduced vocal quality, and word-finding difficulties, have been frequently observed in individuals with heightened anxiety. Understanding the mechanisms underlying this association is important for both clinical and linguistic practice. Objective: This narrative review aimed to synthesize existing literature on the relationship between anxiety and phonological speech impairments, focusing on neurobiological, physiological, and cognitive mechanisms, and to highlight implications for clinical management. Methods: Relevant studies were identified through searches of PubMed, PsycINFO, Scopus, and Google Scholar. Inclusion criteria emphasized empirical studies, reviews, and theoretical papers addressing anxiety and speech production processes. Findings were organized thematically into domains of neurobiological substrates, phonological speech impairments, and linking mechanisms. Results: Evidence suggests that hyperactivation of the amygdala, dysregulation of the hypothalamic–pituitary–adrenal axis, and altered prefrontal control reduce resources available for speech planning and execution. Anxiety-related physiological changes—such as muscle tension, shallow breathing, and elevated stress hormones—further compromise articulatory precision, prosody, and vocal quality. Cognitive interference and excessive self-monitoring contribute to disfluency, word-finding difficulties, and rate abnormalities. Although consistent associations are reported for stuttering and voice changes, evidence for cluttering and long-term effects remains limited. Conclusion: Anxiety contributes to phonological speech impairments through multifactorial pathways involving neurobiology, physiology, and cognition. Findings support an association rather than causation, with variability across individuals and contexts. Clinical practice should integrate speech-motor interventions with psychological support to address both anxiety and speech outcomes. Further longitudinal and ecologically valid studies are needed to clarify mechanisms and optimize treatment.
Keywords: Anxiety Disorders; Phonological Speech Impairments; Stuttering; Cluttering; Voice Quality; Anomic Aphasia; Neurobiology of Speech